2014
DOI: 10.1371/journal.ppat.1004440
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Challenge with an SIV-Based Dual Reporter System Reveals That Infection Can Occur throughout the Upper and Lower Female Reproductive Tract

Abstract: The majority of new HIV infections occur in women as a result of heterosexual intercourse, overcoming multiple innate barriers to infection within the mucosa. However, the avenues through which infection is established, and the nature of bottlenecks to transmission, have been the source of considerable investigation and contention. Using a high dose of a single round non-replicating SIV-based vector containing a novel dual reporter system, we determined the sites of infection by the inoculum using the rhesus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 39 publications
11
111
0
Order By: Relevance
“…We first examined CD3 expression in 4 animals where foci of infection were identified. Of 229 SIVmac239 infected cells characterized, 75.1% (172) of were CD3+, consistent with our previous study (Stieh et al, 2014). This indicates a significant portion of CD3 negative target cells (24.9%) including macrophages and dendritic cells (DCs) are infected during or shortly after transmission.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We first examined CD3 expression in 4 animals where foci of infection were identified. Of 229 SIVmac239 infected cells characterized, 75.1% (172) of were CD3+, consistent with our previous study (Stieh et al, 2014). This indicates a significant portion of CD3 negative target cells (24.9%) including macrophages and dendritic cells (DCs) are infected during or shortly after transmission.…”
Section: Resultssupporting
confidence: 91%
“…The 48-hour time point provides a “snapshot” into the state of SIV infection very early after challenge, before widespread systemic response to the virus. This time point was chosen as it was the earliest interval at which we could reliably detect reporter expression (Stieh et al, 2014). Reproductive tracts were removed, soaked in luciferin to reveal luciferase expression and sites of infection were detected using an in vivo imaging system (IVIS) as previously described (Stieh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with ‘treatment as prevention’, the anti viral agents must be present in sufficient concentration to eliminate all potential T/F viruses from establishing a sustained infection. Studies of non-human primates suggest that these target cells are at or near the genital mucosal surfaces 113 , but more distant cells throughout the female reproductive tract (including the ovaries) may be exposed to virus and infected 114 .…”
Section: Bottlenecks Inform Prevention Strategiesmentioning
confidence: 99%
“…Using a unique method to identify distinct HIV-1 particles without the encumbrance of tissue autofluorescence, we demonstrated that HIV-1 can penetrate both the vaginal and ectocervical stratified squamous and endocervical simple columnar epithelia of the lower FRT (15). For a productive infection to occur, HIV-1 must efficiently traverse these epithelia to reach target cells (16)(17)(18) located in the intra-or subepithelial compartments (15,19). We took advantage of our ability to study the interaction of HIV-1 with mucosal sites to study the influence of SEVI on the diffusion of HIV-1 in FRT tissues.…”
mentioning
confidence: 99%